Thermal properties of carbon nanofibers enhanced lightweight cementitious composite under high temperature - Wang, Su (2022)
Foam concrete is conventionally used in non-structural applications (e.g. thermal and acoustic insulation) due to its lightweight nature and poor mechanical properties. However, interest in adopting foam concrete as structural components has increased phenomenally in recent years due to its lightweight and sustainable feature. A new type of foam concrete termed as carbon nanofibers enhanced lightweight cementitious composite (CNF-LCC) was developed by blending micro-foam bubbles with carbon nanofibers enhanced ultra-high performance concrete; it has superior mechanical properties, long-term properties and bond performance with steel bar compared with conventional foam concrete. In this paper, thermal properties of CNF-LCC during heating were investigated and compared with normal weight concrete (NWC) and lightweight aggregate concrete (LWAC). From room temperature to 800 ℃, the thermal diffusivity of CNF-LCC was lower than NWC and similar to LWAC while the specific heat and thermal conductivity of CNF-LCC was lower than both NWC and LWAC. CNF-LCC showed better structural efficiency than NWC and LWAC in combination of mechanical and thermal insulation properties. The measured thermal insulation properties under high temperature were verified by conducting one-dimensional heat transfer tests and numerical analysis on CNF-LCC blocks. Furthermore, the thermal strain of CNF-LCC during heating is lower and more stable than NWC and LWAC. Dehydration reaction at isothermal elevated temperature was characterised for the analysis of experimental results. Foam bubbles could reduce both thermal insulation and strain properties while a low dosage of CNFs had minimum effect on the thermal insulation properties but could improve the mechanical properties and decrease the thermal shrinkage. CNF-LCC showed potential for fire resistant as a structural lightweight concrete due to the excellent thermal insulation and lower thermal strain properties.